The Salish Weave Box Sets: Art and Storytelling Project at SFU's Indigenous Curriculum Resource Centre - Edwards, Ashley; Vance, Courtney (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2024)
The Salish Weave Box Sets: Art and Storytelling Project was conducted for the Indigenous Curriculum Resource Centre (ICRC) at Simon Fraser University (SFU) Library, with the goal of providing resources to include Indigenous art in the post-secondary classroom. The project looked at the concept of art as literature, using the concept of Indigenous Storywork (Archibald, 2008). In this paper, we provide further context about the ICRC at SFU Library and the Salish Weave Box Sets, and we present the approach, project themes, and lessons learned from the Salish Weave Box Sets: Art and Storytelling Project.